Clinical Study of the Role of Differential Blood Count as a Pretreatment Diagnosis for Patients With Diffuse Large B Cell Lymphoma (DLBCL) - Wahab, John; Ai, Limei; Shanshan, Yu; Zekrumah, Marcilinus (Journal of Biology and Life Science, 2023)
The study employed simple differential blood count assessing clinical prognosis index at diagnosis of DLBCL patients. Each patient’s prognostic performance status was computed using absolute neutrophils/absolute lymphocytes(ANC/ALC), absolute lymphocytes/absolute monocyte (ALC/AMC), and absolute platelet/absolute lymphocytes APC/ALC) respectively, and then compared to preexisting parameters IPI, ECOG-PS, KI-67% protein expression, LDH, gender, bone marrow infiltration, and tumor location using ROC curves to determine the sensitivity and specificity threshold of each CBC performance index and survival analysis to estimate 5-year PFS and OS. The study showed that NLR compared to LDH at NLR ≥ 3.50 correlates to an increase in LDH >230UI/L, ECOG-PS score 2-4, increase in nodal tumor location, and elevation in cell proliferation at ki-67% protein expression (≥20%) at diagnosis exhibit poor prognosis to R-CHOP chemotherapy. Our results also demonstrated that LMR≤2.50 was associated with ECOG-PS score 2-4, increased number of extranodal tumor locations, in comparison with gender female participants had high sensitivity 60%, also low score LMR≤ 2.50 correspond to IPI score 3-5 among DLBCL patients. Our results further revealed that Pretreatment PLR≥150 at diagnosis correlates with LDH>230UI/L, and an ECOG-PS score of 2-4 in DLBCL patients.